Two Functional Classes of Rod Bipolar Cells in the Healthy and Degenerated Optogenetically Treated Murine Retina - Schilardi, Giulia; Kleinlogel, Sonja (Frontiers in Cellular Neuroscience, 2022)
Bipolar cells have become successful targets for optogenetic gene therapies that restore vision after photoreceptor degeneration. However, degeneration was shown to cause changes in neuronal connectivity and protein expression, which may impact the quality of synthetically restored signaling. Further, the expression of an optogenetic protein may alter passive membrane properties of bipolar cells affecting signal propagation. We here investigated the passive membrane properties of rod bipolar cells in three different systems, the healthy retina, the degenerated retina, and the degenerated retina expressing the optogenetic actuator Opto-mGluR6. We found that, based on the shape of their current-voltage relations, rod bipolar cells in healthy and degenerated retinas form two clear functional groups (type 1 and type 2 cells). Depolarizing the membrane potential changed recorded current-voltage curves from type 1 to type 2, confirming a single cell identity with two functional states. Expression of Opto-mGluR6 did not alter the passive properties of the rod bipolar cell. With progressing degeneration, dominant outward rectifying currents recorded in type 2 rod bipolar cells decreased significantly. We demonstrate that this is caused by a downregulation of BK channel expression in the degenerated retina. Since this BK conductance will normally recover the membrane potential after RBCs are excited by open TRPM1 channels, a loss in BK will decrease high-pass filtering at the rod bipolar cell level. A better understanding of the changes of bipolar cell physiology during retinal degeneration may pave the way to optimize future treatment strategies of blindness.